Pengaruh Fitur Arsitektur, Fitur Interior Dan Fasilitas Penunjang Terhadap Shopping Value - Michaela Leoda Wijaya; Ricky Chia; Sabrina Oktaria Sihombing (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2020)
Backgorund - The growing middle class society is growing and the growth of shopping centres has now become a phenomenon in Indonesia. The increase in purchasing power is related to the consumptive pattern which is an indicator of the classification of the middle class in a society. Implicitly this can indicate that the development of shopping centres in Indonesia is influenced by the growth of the middle class in Indonesia. Aim - This study aims to examine the relationship between architectural features, interior features, and supporting facilities on shopping value. Design / methodology / approach - This study uses a non-probability sampling method, namely convenience sampling. This study included 130 respondents. Data collected by conducting surveys. The analysis technique used in this study is multiple linear regression analysis. Finding - The results show that two of the three hypotheses are supported. The hypothesis is the relationship between interior features and shopping value, and the relationship between supporting facilities and shopping value. Research Implication – Managerial implications of the results of this study are to encourage increased comfort associated with architectural features such as the lobby or a comfortable entrance position. This increased comfort is also related to the material used in the architecture. Limitation - This research cannot be separated from the limitations of the study as follows. First, this study uses a non-probability sampling design in which the results of the study cannot be generalized. Secondly, this study only uses one mall.